Improving the Students’ Pronunciation Ability by Using Elsa Speak App - Nur Wahid Akhmad; Ahmad Munawir (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
The purpose of this study was to determine the improvement of students' pronunciation skills (Supra-segmental) in English using the ELSA Speak application and to determine student perceptions of the use of the ELSA Speak application. The location of this research is at the University of West Sulawesi. The approach used in this research is quantitative. The methodology used in this study is the One Group Pre-experimental design. The population in this study was class D class 2021 majoring in English at the University of West Sulawesi. The sampling method used in this study is a simple random sampling method. The research sample used was 20 people. The research data was collected through a pronunciation test given to students using pre-test and post-test as well as distributing perception questionnaires to students. The data in this studywere analyzed using non-parametric analysis in the form of a T-test through SPSS. The students' pre-test means the score is 52.30 while the post-test mean score is 65.60. while the results of the T-test showed that sig. (2-tailed = 0.000) <0.05. That means the ELSA Speak application can significantly improve students' pronunciation skills in English. The results of the perception questionnaire are 82% which is included in the good category. This means that students respond well to the use of the ELSA Speak application.